The performance of surface barrier discharge in magnetic field driven by half bridge series resonance converter - Fri Murdiya; Febrizal Febrizal; Amun Amri (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2017)
This paper reports an application of a series resonance converter as a high voltage generator to drive a surface barrier discharge with a magnetic field. The high voltage was about 5 kV with the frequency of 25 kHz. It was connected to circular aluminum plates as the anode electrode and a rectangular aluminum plate as the cathode electrode. These electrodes were separated by a glass dielectric as the barrier. The experiment result indicated that the discharge current with magnetic field was lower than without magnetic field. The plasma on the surface barrier with magnetic field was more luminous than without magnetic field. It also indicated that the area of Lissajous diagram for the surface barrier discharge with magnetic field was slightly decreased than without magnetic field. It could be concluded that the magnetic field affects the plasma progress on the surface barrier. Molecular dynamic (MD) could be used in understanding the ionization process of air molecules. The ionization energies for CO2, N2, and O2 were 0.0502 kcal/mol, 0.0526 kcal/mol and 0.430 kcal/mol, respectively in 1,000 seconds. The highest ionization energy was O2.